Unobstructed orthopaedic surgical robot assisted percutaneous iliosacral screw fixation of sacral brittle fractures - Hao, Xiao-dong; Zhang, Yuan-zhi; Wang, Shao-bai; Liu, Gang (Frontiers in Medicine, 2023)
Pelvic fractures mostly result from high-energy injuries in life; the longitudinal fracture of the sacrum is the most common type of sacrum fracture. This study was designed to evaluate the accuracy, safety, and efficacy of percutaneous sacroiliac joint screw placement in the treatment of longitudinal sacrum fractures with the assistance of unobstructed orthopaedic surgery robots. According to different surgical methods, 32 patients were divided into robot group and free hand group, with 16 patients in each group. The operation time, intra-operative blood loss, intra-operative fluoroscopy times, screw placement angle deviation were collected. There were statistically significant differences in terms of angle deviation of screw placement (1.96±0.75° vs 2.87±1.03°; P=0.0145), deviation of the guide needle (1.92±0.93mm vs 2.91±1.22mm; P=0.0209), intra-operative fluoroscopy time (7.25±1.72s vs 20.93±5.64s; P=0.0000), insertion time of each sacroiliac joint screw (14.72±2.66min vs 29.21±5.18min; P=0.0000). There was no statistically significant difference in terms of blood loss (100.21±7.37ml vs 102.52±8.15ml; P=0.4136). These results suggest that orthopaedic surgery robot for the treatment of longitudinal sacrum fracture is safer and provides less irradiation than the traditional freehand methods.